PSYCHOLOGY OF PRESCHOOL CHILDREN AND ITS LEARNED STATUS - Dilshoda Kuliyeva Safarovna (Лучшие интеллектуальные исследования, 2023)
Annotation: This article explores the intricate psychology of preschool children and the learned status of their behaviors and cognitive processes. The study delves into the existing literature, analyzes relevant research methods, presents findings from empirical studies, and discusses the implications for the broader understanding of preschooler development. The goal is to shed light on the complexities of preschool psychology and how learned behaviors play a crucial role in shaping their cognitive, emotional, and social capacities.